2012
DOI: 10.1103/physrevb.85.174428
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between propagating spin waves and domain walls on a ferromagnetic nanowire

Abstract: We numerically investigate the interaction between propagating spin waves and a transverse domain wall in a nanowire by using micromagnetic simulations. In order to understand the mechanisms that lead to domain wall motions, we calculate domain wall velocity in a defect-free nanowire and the depinning fields for a pinned domain wall that is depinned in and against the direction of the spin-wave propagation. We find that the physical origin of the spin-wave-induced domain wall motion strongly depends on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 23 publications
2
67
1
Order By: Relevance
“…However, the contrary was found in literature [13][14][15][16]: magnons push DWs to move along with them. The counteraction force due to linear MT between magnons and DWs could be a possible explanation for this phenomenon.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…However, the contrary was found in literature [13][14][15][16]: magnons push DWs to move along with them. The counteraction force due to linear MT between magnons and DWs could be a possible explanation for this phenomenon.…”
contrasting
confidence: 48%
“…The counteraction force due to linear MT between magnons and DWs could be a possible explanation for this phenomenon. Kim et al [16] employed a similar argument to shed light on the observed drag of DW by magnons in micromagnetic simulation. Wang et al [13] included the counteraction force phenomenologically in a 1D model to understand micromagnetic simulation results, and found qualitative agreement between model and simulation.…”
mentioning
confidence: 99%
“…A combination of a strong MOKE signal and low magnetic damping in an insulating material would not only be of interest for magneto-optic applications. This would also allow one to investigate novel phenomena such as domain-wall motion in a magnetic insulator, which is in contrast to the well-established domain-wall motion in conductors, not driven by electronic spin currents [27] but by spin waves [28,29]. Recent results in the field of spin caloritronics have shown that the spin waves can also be thermally excited by the spin Seebeck effect [30] and are capable of moving magnetic domains [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of DW propagation direction, the pure magnonic STT predicts [15] a DW moving against magnon propagation direction. However, a DW may also propagate along magnon flow direction [17][18][19]. This is very similar to electric-current-driven DW motion: A DW propagates along or against electron flow direction, depending on detailed spin-orbit interactions and DW types [20][21][22].…”
mentioning
confidence: 99%